Study on the fruit Morphology of Mapania species (Cyperaceae)Eastern North of Sarawak - Meekiong, Kalu; Miraadila, Mohd Isa; Zinnirah, Shabdin; Geradlyn, Ivy; Aimi Syazana, Sedek; Syauqina Syasya, Binti Mohd Yusoff (Forest Department Sarawak, 2019)
The study of fruit marpholqy of Mapania species fram Eastem North of Sarawak is presented in this paper. The samples were collected from various Localities in the Eastern North of Sarawak, includes Lambir Hills National Park (LHNP), Bukit Sembiling Nature Reserve (BSNR), Ulu Mentawai, Mulu National Park (UMMNP), Long Banga (LB) and Tama Abu Production Farest TAPF)" Matured fruits were obtained by dissecting the spike. Morphalogical characteristics were observed use USB Portable Microscapes (500x) and parameters were measured use digital caliper. The morphological characteristics were compared and analyzed. Fruits of M. meditensis were the biggest (9 mm long, 4.25 mm diam.) and the smallest fruit was M. debilis (2.45 mm long, 1.5 mm diam.). Overall the fruit morphalagical was very useful to differentiate the species level particularly the sizes, exocarp appearance and the present of costae.